The Magnified Imperfection : The Relationship between Body Dysmorphic Disorder and Self-Acceptance of Vocational School Students - Akbar Fillah; Yuda Syahputra; Tanti Ardianti (Asosiasi Asesmen Pendidikan (AAP), 2026)
This study aims to provide an overview and determine the relationship between Body Dysmorphic Disorder and Self-Acceptance in Students of SMK Pembangunan Jaya Yakapi. The research was conducted using quantitative methods. The data and sources in this study were students at SMK Pembangunan Jaya Yakapi, totaling 275 students and were determined to be the source of research data, this research was a random sampling study. The author's data analysis technique uses Linear Regression by collecting data, processing data, and interpreting data. The results of data interpretation values through Pearson correlation analysis show a significant negative relationship between Body Dysmorphic Disorder (BDD) and Self-Acceptance (SA) in students, with a correlation coefficient of r = -0.674 and a significance level of p = 0.000. The correlation coefficient value is included in the strong category which indicates that the higher the level of BDD that students have, the lower the level of self-acceptance.